Eksplorasi Efektivitas Sistem Layanan Administrasi di PT Taspen (Persero) Kantor Cabang Bandung - Masrifah, Siti (Jurnal Digital Bisnis, Modal Manusia, Marketing, Entrepreneurship, Finance, & Strategi Bisnis (DImmensi), 2025)
This study explores the effectiveness of the administrative service system implemented by PT Taspen (Persero) KC Bandung through the use of Taspen One Hour Online Services (TOOS) and Taspen Digital Enterprise Services (TDES). The research was conducted during an internship program in the administration division, focusing on the management of participants' claims and non-claims. The results show that both systems successfully improved service efficiency by speeding up the claims submission process and monitoring the submission status. However, there are challenges such as reliance on internet connectivity and limited system capacity, which resulted in decreased participant satisfaction. Therefore, further optimization of technological infrastructure and improvement of participants' digital literacy are needed to maximize system performance. This study is expected to contribute to the further development of technology-based administrative systems and improve service efficiency for participants.